A dynamic surgical navigational approach for immediate implantation and transcrestal sinus augmentation - Sanjay Jain; Akshita Solanki (Wolters Kluwer Medknow Publications, 2021)
Real-time dynamic navigation shows various advantages over static guides in the placement of dental implants. The goal of this article is to highlight a safe and alternative approach for transcrestal sinus augmentation and immediate implantation by dynamic navigation. It elaborates and defines numerous advantages of the trace and place workflow over the fiducial technique in dynamic navigation. The usage of osseodensifying burs were shown to have higher bone-implant contact, stability, and insertion torque. Their application allows drill-tip calibration that can thus be used for dynamic navigation allowing a real-time surgical evaluation for the implant placement. This article describes a novel technique for transcrestal sinus augmentation during implant placement with osseodensifying burs using dynamic navigation.